Thinning, crown-reducing and abundance-promoting pruning method for juglans siggillata - ZHAO CHUAN; LI JUNNAN; LIANG LINBO; LU BIN; XIONG XINWU; XU LIANG; FENG QIAN; SU LIANBO; ZHANG YU; HAO JIABO (2021)
The invention discloses a thinning, crown-reducing and abundance-promoting pruning method for juglans siggillata. The thinning, crown-removing and abundance-promoting pruning method for juglans siggillata comprises the following steps of observing and remaining branches, sawing off miscellaneous branches, cutting off diseased branches, protecting wounds and the like. The method can remove inner bore upright branches, enables a round-head tree to form a bowl shape, and promotes large branches to germinate and bear fruits inside, outside, above and below. The method is mainly used for implementing a big branch pruning technology for reducing crowns, opening angles of large branches and correcting tree body skeletons for adult juglans sigillata and is used for solving problems of inter-row closing, inter-plant closing and inner bore closing of a walnut orchard and promoting three-dimensional fruiting of the crowns. The labor-saving pruning method focuses on sawing off overdense large branches influencing illumin